Modulating electronic structure of CoP electrocatalysts towards enhanced hydrogen evolution by Ce chemical doping in both acidic and basic media. (August 2017) - Gao, Wei; Yan, Ming; Cheung, Ho-Yuen; Xia, Zhaoming; Zhou, Xuemei; Qin, Yuanbin; Wong, Chun-Yuen; Ho, Johnny C.; Chang, Chun-Ran; Qu, Yongquan
Abstract: Doping foreign metal ions into catalysts is considered as an effective approach to optimize the catalytic sites and improve their performance. Here, we develop and demonstrate the concept of rare-earth elemental doping by Ce into host catalysts of CoP in modulating their electronic structures and decreasing their adsorption free energy of hydrogen for the enhanced hydrogen evolution reaction (HER) performance via a complementary theoretical and experimental approach. In contrast to undoped catalysts, the Ce-doping can facilitate lower overpotential, Tafel slope and charge transfer resistance as well as larger electrochemically active surface area and turnover frequency to deliver superb catalytic activity and stability. In particular, the catalyst with optimized doping amount exhibits ultra-low overpotentials of 54 and 92 mV at 10 mA cm −2 in acidic and basic media, respectively, among many recently-reported CoP-based catalysts. Doping Ce into CoP not only illustrates benefits in improving the catalytic property for HER, but also opens up a novel view of doping rare earth elements into electrocatalysts for regulating their physiochemical and electrochemical properties. Graphical abstract: Theoretical analysis and experimental results demonstrated the significant enhancement in catalytic properties for electrochemical hydrogen evolution caused by doping Ce into CoP electrocatalysts in both acidic and basic electrolytes. Highlights: DFT analyses showed decreased hydrogen adsorption energy and modified Bader charge of Co for Ce-doped CoP would benefit HER. Electrochemical results confirmed the enhanced catalytic properties of Ce-doped CoP to boost HER in acidic and basic media. Superb performances with low overpotentials of 54 and 92 mV @ 10 mA cm -2 in both acidic and basic media for Ce-doped CoP.